La transition énergétique : eldorado des relations ville-campagne ? Le cas de TEPOS métropole-montagne - François Balaye; Lisa Bienvenu; Gilles Debizet; Pierre-Antoine Landel (Revue de Géographie Alpine)
Changing energy production patterns are posing a challenge to the relations between rural territories, where production could potentially exceed consumption, and their urban counterparts, where the opposite tends to hold true. Energy flows between places of production and places of consumption have largely been considered from the point of view of networks and less from the perspective of the institutional relations between territories. This article analyses transactions between cities and upland institutions carried out within the framework of the “Territoires à Energie Positive” (Positive Energy Territories) – or TEPOS – process in France’s Auvergne-Rhône-Alpes region.There is a disconnect between the TEPOS topics and the reality of the flows, and it underlines the gap between the promise of rural/urban complementarity (called by energy transition policies) and the weak position of the TEPOS within a mosaic and juxtaposition of decision-making arenas pertaining to spatial planning or energy carriers. Thanks to its agility and creativity, the TEPOS process could find relevance and sustainability, in addition to institutionalised planning that - variously and slowly - incorporates the energy transition aims.